Harnessing Genetic Diversity in Saccharomyces cerevisiae for Fermentation of Xylose in Hydrolysates of Alkaline Hydrogen Peroxide-Pretreated Biomass - Sato, Trey K. (American Society for Microbiology, 2014)
The fermentation of lignocellulose-derived sugars, particularly xylose, into ethanol by the yeast Saccharomyces cerevisiae is known to be inhibited by compounds produced during feedstock pretreatment. We devised a strategy that combined chemical profiling of pretreated feedstocks, high-throughput phenotyping of genetically diverse S. cerevisiae strains isolated from a range of ecological niches, and directed engineering and evolution against identified inhibitors to produce strains with improved fermentation properties. We identified and quantified for the first time the major inhibitory compounds in alkaline hydrogen peroxide (AHP)-pretreated lignocellulosic hydrolysates, including Na(+), acetate, and p-coumaric (pCA) and ferulic (FA) acids. By phenotyping these yeast strains for their abilities to grow in the presence of these AHP inhibitors, one heterozygous diploid strain tolerant to all four inhibitors was selected, engineered for xylose metabolism, and then allowed to evolve on xylose with increasing amounts of pCA and FA. After only 149 generations, one evolved isolate, GLBRCY87, exhibited faster xylose uptake rates in both laboratory media and AHP switchgrass hydrolysate than its ancestral GLBRCY73 strain and completely converted 115 g/liter of total sugars in undetoxified AHP hydrolysate into more than 40 g/liter ethanol. Strikingly, genome sequencing revealed that during the evolution from GLBRCY73, the GLBRCY87 strain acquired the conversion of heterozygous to homozygous alleles in chromosome VII and amplification of chromosome XIV. Our approach highlights that simultaneous selection on xylose and pCA or FA with a wild S. cerevisiae strain containing inherent tolerance to AHP pretreatment inhibitors has potential for rapid evolution of robust properties in lignocellulosic biofuel production.